2007
DOI: 10.1677/erc-07-0061
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine-like prostate cancer cells: neuroendocrine transdifferentiation of prostate adenocarcinoma cells

Abstract: Neuroendocrine (NE) cells represent a minor cell population in the epithelial compartment of normal prostate glands and may play a role in regulating the growth and differentiation of normal prostate epithelia. In prostate tumor lesions, the population of NE-like cells, i.e., cells exhibiting NE phenotypes and expressing NE markers, is increased that correlates with tumor progression, poor prognosis, and the androgen-independent state. However, the origin of those NE-like cells in prostate cancer (PCa) lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
184
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(197 citation statements)
references
References 94 publications
7
184
1
1
Order By: Relevance
“…In the latter, the increased number of NE cells in advanced prostate tumors are frequently observed in HRPC after long-term androgen deprivation therapy. 46 It has been reported that several factors secreted from NE cells induce cell proliferation and the expression of oncogenes but cell culture studies have shown no effect or even an inhibitory effect on cell growth and a lack of aggressiveness in normal epithelial cells. This has led to some investigators to suggest that these NE cells observed in PCa may have a different origin and should be considered as NE-like PCa cells and not NE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, the increased number of NE cells in advanced prostate tumors are frequently observed in HRPC after long-term androgen deprivation therapy. 46 It has been reported that several factors secreted from NE cells induce cell proliferation and the expression of oncogenes but cell culture studies have shown no effect or even an inhibitory effect on cell growth and a lack of aggressiveness in normal epithelial cells. This has led to some investigators to suggest that these NE cells observed in PCa may have a different origin and should be considered as NE-like PCa cells and not NE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most significant histological variant is neuroendocrine prostate cancer, which is generally classified as either small cell carcinoma or a carcinoid tumor, and represents <2% of prostate cancer cases (Grignon 2004). However, focal regions of neuroendocrine differentiation are more commonly observed in prostate adenocarcinoma, particularly following recurrence after prostatectomy and androgen deprivation therapy (Yuan et al 2007;Komiya et al 2009), and expression of the neuroendocrine marker chromogranin A is associated with the development of castration-resistant tumors and shortened time to disease recurrence (Kokubo et al 2005;Berruti et al 2007). This prevalence of neuroendocrine differentiation after recurrence may be due to the lack of AR expression by neuroendocrine cells, which are inherently castration-resistant.…”
Section: Subtypes Of Prostate Cancermentioning
confidence: 99%
“…PSMA ligand PET/CT has an evolving role in PSMA-targeting treatments (e.g., radioligand therapy), evaluating target expression and therefore potentially predicting response (62)(63)(64). A rare but potential limitation is absent or low PSMA expression (e.g., in visceral metastases) in advanced disease, which may be related to therapy-induced specific biologic subtypes (e.g., neuroendocrine differentiated PC) (65,66). Further information on the use of PSMA ligands for diagnosis has been published elsewhere (67,68).…”
Section: Advanced Diseasementioning
confidence: 99%